One Health WASH: an AMR-smart integrative approach to preventing and controlling infection in farming communities - Jiménez, C.E.P.; Keestra, S.M.; Tandon, P.; Pickering, A.J.; Moodley, Arshnee; Cumming, O.; Chandler, C.I.R. (BMJ, 2023)
While the One Health framework is now widely accepted as a strength in understanding antimicrobial resistance (AMR), its application in intervention design to prevent and control drug-resistant infections across humans, animals, and the environment remains weak. The potential for infection prevention and control measures to contribute to the AMR agenda is recognised in rhetoric, but evidence to guide action is patchy and uncoordinated. While water, sanitation, and hygiene (WASH) and on-farm biosecurity interventions are key strategies for preventing and controlling infections, they are frequently implemented separately for humans and animals. We argue for integration across these sectors to improve planning for AMR control.